Effect of Microstructure on mechanical and Charpy impact properties offerrite-martensite dual phase API X52 pipeline Steel - BOUTESSOUNA, Belkacem (International Journal of Computational and Experimental Science and Engineering, 2017)
The microstructural changes that occur during intercritical annealing treatment at 780°C of API X52 steel have been investigated. Three treatments were developed to produce dual phase (DP) microstructure: Intermediate Quenching Treatment/Air (IQ/A), Intermediate Quenching Treatment/Water (IQ/W) and Step Quenching Treatment (SQ). The IQ/W resulted in the formation of fine and fibrous martensite morphology uniformly distributed in the ferrite matrix. However, the IQ/A treatment showed a spherical network of martensite along the ferrite/ferrite grain boundaries. The SQ yielded blockly and banded martensite and ferrite morphology. The experimental results show that API X52 (DP) steel with finely dispersed microstructures (IQ/W) have higher Charpy impact properties and lower ductile–brittle transition temperature (DBTT) than (DP) steel with banded microstructures. A carefully conducted comparison of fracture surfaces of the representative specimens obtained after IQ and SQ treatments has been studied.